Cryptocurrency as digital asset according to the principles of Usul Al-fiqh: a critical analysis by Mohd Daud Bakar - Muhamad Ibrahim, Najhan; Abu Bakar, Munira; Drs Nasrul, Muhammad Amrullah; Abdul Rahman, Siti Sarah (IEEE, 2024)
The article provides a critical assessment of cryptocurrencies as digital assets within the framework of Islamic legal theory, or Usul al-Fiqh. The researcher is none other than Mohd Daud Bakar, a renowned authority on Islamic law and finance. The rise in popularity of cryptocurrencies as a digital representation of wealth has raised questions about whether they are consistent with Islamic principles and financial ethics. Both contemporary legal theories and the foundations of traditional Islamic jurisprudence are thoroughly examined in order to evaluate the nature of cryptocurrencies. To determine its classification and legitimacy under Islamic law, it takes into account the key features of cryptocurrencies, such as decentralisation, cryptographic security, and digital scarcity, within the framework of Usul al-Fiqh principles. The research also examines the potential impact of cryptocurrencies on the broader Islamic financial industry, considering its potential applications as a medium of exchange, investment instrument, and store of wealth. It also addresses the advantages and disadvantages of cryptocurrencies in the context of Islamic finance, particularly in relation to riba (usury), gharar (uncertainty), and haram (prohibited) activities. In summary, by supplying details on cryptocurrency legal classification, acceptability as digital assets, and consequences for Islamic financial principles, this research contributes to the ongoing conversation concerning cryptocurrencies in the framework of Islamic law.